Operasi Dasar Baris/Kolom Matriks Secara Interaktif Dengan Menggunakan R - I Gusti Agung Anom Yudistira; Rinda Nariswari (Bina Nusantara University, 2023)
The linear algebra applications available today usually only provide the result. So, it is a challenge to overcome this, and innovation is needed in the computing aspect. One of the popular and open-source programming languages ​​is R. The computational innovation in R needs to be explored further, to explore the R programming logic. The creation of a function environment with the list function and the involvement of local and global variables/objects has received little attention. Based on the problems formulated, this study proposes two objectives, namely (1) developing an R program that is able to provide interactive and step-by-step solutions, to obtain a solution of a system of linear equations, and (2) to explore R’s ability to create and handle global variables. An R program is created, starting with creating a function environment. This function environment is filled with four related functions, namely “exchange”, “multiply”, “fold”, and “yield”. These four functions are connected to each other through a global object. Users can type in each function to perform row/column operations, interactively and step by step. The environmental function in this program, is named OBE. The OBE function accepts input in the form of a coupling matrix derived from a system of linear equations. The final result of this interactive process chain is given by the “result” function. The result function will display two matrices, namely the Original Matrix which is the input and the Equivalent Matrix.